2017
DOI: 10.1007/s00270-017-1589-1
|View full text |Cite|
|
Sign up to set email alerts
|

Short-Segment Coil Embolization Using a Double-Balloon Technique in an Experimental Vascular Model

Abstract: PurposeTo evaluate the feasibility of short-segment coil embolization between 2 balloons for tight packing in an experimental vascular model.Materials and MethodsThree coil embolization techniques were performed by 5 interventional radiologists as follows: (1) proximal balloon technique (proximal BT) which involved proximal balloon inflation and coil deployment over the balloon, (2) distal balloon technique (distal BT) which involved distal balloon inflation and coil deployment at the proximal side of the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…However, it is thought that the transvenous balloon-assisted technique is useful when coil migration to the frame outside is considerable. Short-segment coil embolization using double balloon technique in an experimental vascular model has been reported, 19) and we performed double balloon technique with reference to it. Moreover, finishing coils migrate easily to the ICA; thus, transarterial balloon is slightly overinflated.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is thought that the transvenous balloon-assisted technique is useful when coil migration to the frame outside is considerable. Short-segment coil embolization using double balloon technique in an experimental vascular model has been reported, 19) and we performed double balloon technique with reference to it. Moreover, finishing coils migrate easily to the ICA; thus, transarterial balloon is slightly overinflated.…”
Section: Discussionmentioning
confidence: 99%
“…Short-segment embolization is a relatively difficult procedure, and various techniques have been reported. 14 Yunaiyama et al 1 used a double-balloon technique in an experimental model; however, coil embolization is associated with a risk of coil migration in high-flow vessels, and more stable embolization methods are needed, such as a microvascular plug. Koganemaru et al 4 reported an internal coil packing method for a mesh occlusion device, which is similar to our procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrashort-segment embolization is a highly useful technique [1][2][3][4] ; however, its application in large-diameter target vessels is very difficult because the flow through these vessels is very high. The Amplatzer Vascular Plug 1 (AVP1; Abbott Vascular, Redwood City, CA, USA) is one of the best devices for short-segment embolization, but vessel occlusion can be delayed or fail altogether under certain circumstances, especially in the presence of antiplatelet and/or anticoagulation therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This method can embolise the target artery more tightly and compactly than the proximal balloon occlusion technique. 5 As a result, it also prevented occlusion of the collateral branch that supplies blood flow distally. 2 Also, the original 4.5 Fr guiding sheath system was used, so only a single approach via the right femoral artery was required.…”
Section: Discussionmentioning
confidence: 99%